Social origin and secondary labour market entry: Ascriptive and institutional inequalities over the early career in Italy and Germany. (February 2022) - Barbieri, Paolo; Gioachin, Filippo
Highlights: The flexibilisation in Italy and Germany has exacerbated inequalities between primary and secondary labour markets. The aversion to downward mobility lead to hypothesise mechanisms of compensation for penalty linked to initial instability. We compare the career development of service- and working-class entrants who began with a similar socioeconomic status. Social origin contributes to unequal trajectory developments in both contexts, especially for the low- and middle-educated. University reduces the flexibility penalty in Italy. For German graduates, initial instability leads to more-rewarding jobs. Abstract: This paper investigates how labour market flexibilisation strengthens the role of social origin in conditioning inter- and intragenerational mobility chances. Drawing on the upper-class aversion to downward mobility, we explore mechanisms through which advantaged social origin directly compensate for the socioeconomic penalty that arises from initial contractual instability over the career. Conversely, we examine whether a bad start for less-socially privileged entrants represents a source of cumulative disadvantage. The Italian and German labour markets are compared since optimal national cases of labour market duality and rigidity yet differing in their educational and labour market institutions and mobility regimes. We perform growth curves under a matching framework to counterfactually compare the career development of service- and working-class entrants in the two countries, who began with similar socioeconomic status. We reveal that social origin contributes to unequal trajectory developments in both contexts, especially for the low- and middle-educated. No significant DESO over the career emerges among degree holders in either country. Finally, attending university entirely reduces the flexibility penalty in Italy, whereas for German graduates, initial instability serves as a gateway to more prestigious jobs.